Effect of dietary supplementation of ginger on feed conversion ratio, carcass physiognomies and haematological parameters in broiler (Research in Agriculture Livestock and Fisheries, 2017)
This study evaluated the effect of ginger on the growth performance, carcass quality of broiler chickens. A total of 40 broiler chickens were randomly selected into four groups identified as A (1% ginger extract), B (2% ginger extract), C (positive control) and D (negative control). All groups contain equal number of birds (n=10.) Birds were treated with aqueous ginger extract via drinking water. Significant variations (p